(untitled) (Indian Journal of Animal Production and Management, 2024)
Thirty two calves consisting of 16 Holstein Friesian crossbred (G1) and 16 Jersey crossbred (G2) were divided into four different groups at one week of age keeping uniformity in breed and sex viz. T1: calves fed on calf starter ration without molasses, T2: calf starter with 20 g, T3: calf starter with 40 g and T4: calf starter with 60 g freshly mixed molasses per kg of feed. The average initial body weight in each group was almost similar. The calf starter ration was fed to calves twice daily ad libitum and soft green fodder such as Para (Bracharia mutica), Napier (Pennisetum purpureum) and Guinea (Panicum maximum) grasses were fed along with soft paddy straw free of choice as basal diet from second week onwards. The experimental calves were fed whole milk manually from a pail at the rate of 1/10th of the body weight till consumption to 0.5 kg calf starter ration (CP: 21% and TDN: 75%) daily. Wholesome potable water was also accessible freely to the calves during the experimental period. The overall average body weight of calves were 47.31± 2.42, 50.56 ± 2.26, 57.63 ± 1.50 and 59.13 ± 1.71 kg at the 97 day of age and the average body weight gain were 0.232 ± 0.021, 0.267 ± 0.019, 0.347 ± 0.012 and 0.363 ± 0.013 kg during 7 to 97 days of age in T1, T2, T3 and T4 groups, respectively. There was significant (P<0.01) difference of average body weight at 97 days and body weight gain during 7 to 97 days of age. The overall average body length was 80.25 ± 0.67, 81.88 ± 1.43, 84.38 ± 0.34 and 87.81 ± 0.43 cm; height at wither was 83.25 ± 0.81, 85.25 ± 1.63, 88.50 ± 0.83 and 90.13 ± 0.91 cm and heart girth was 89.50 ± 1.22, 89.38 ± 1.01, 95.00 ± 0.91 and 102.00 ± 0.95 cm in T1, T2, T3 and T4 groups respectively at 97 days of age. The average body length, height at wither and heart girth were also differed significantly (P<0.01) among the groups. However, significant (P<0.05) effect of breed was observed for height at wither and highly significant (P<0.01) effect of breed was observed for heart girth. There was highly significant (P<0.01) effect of groups and breeds on average daily DM intake, but only groups have highly significant (P<0.01) effect on FCR during the same period. The average daily cost of feeding was lesser in T4 group by Rs. 6.38 than the control group (T1). There was positive correlation of body weight with body length, height at withers and heart girth. The growth performance was better in T4 group in which the calves were fed on calf starter ration mixed with molasses at 6 percent level.